PEMBERDAYAAN MASYARAKAT SENDANGTIRTO DALAM PEMBUATAN PUPUK ORGANIK MELALUI KEGIATAN KKN PPM - Zahrul Mufrodi; Bambang Robi'in; Fiftin Noviyanto (LP2M Universitas Hasanuddin, 2021)
Abstract. Livestock is one of the sizable sources of livelihood in Indonesia which reaches 13.45% of the National Gross Domestic Product (GDP). Sendangtirto is one of the villages in the Sleman district of Yogyakarta with the majority of people having businesses in agriculture and animal husbandry, especially cattle and fisheries. In the village of Sendangtirto there are 13 groups of farmers. The problem faced by the Sendangtirto community is the processing of livestock waste that is not yet optimal for making organic fertilizer. The method used in this PPM KKN activities is counseling about organic fertilizer, the practice of making organic fertilizer from livestock manure, and followed by training in making organic fertilizer product packaging. The purpose of this activity is to provide understanding and skills to the community in managing livestock manure into organic fertilizer. The result of this activity is an increase in understanding and skills of the community in managing livestock manure into organic fertilizer. Increased public understanding of organic fertilizer to 95.65%, increased community skills in making organic fertilizer to 91.30%, and increased community ability to make organic fertilizer product packaging to 86.95%. Abstrak. Peternakan merupakan salah satu sumber mata pencaharian yang cukup besar di Indonesia yang mencapai 13,45% dari Pendapatan Domestik Bruto (PDB) Nasional. Sendangtirto merupakan salah satu desa di kabupaten Sleman Yogyakarta dengan mayoritas masyarakat memiliki usaha di bidang pertanian dan peternakan, khususnya peternakan sapi dan perikanan. Di desa Sendangtirto ini terdapat kelompok peternak yang berjumlah 13 kelompok. Permasalahan yang dihadapi oleh masyarakat sendangtirto adalah pengolahan limbah ternak yang belum optimal untuk membuat pupuk organik. Metode yang dilakukan dalam kagiatan KKN PPM ini adalah penyuluhan tentang pupuk organik, praktek pembuatan pupuk organik dari kotoran ternak, dan dilanjutkan dengan pelatihan pembuatan kemasan produk pupuk organik. Tujuan kegiatan ini adalah untuk memberikan pemahaman dan keterampilan kepada masyarakat dalam mengelola kotoran ternak menjadi pupuk organik. Hasil kegiatan ini adalah terjadi peningkatan pemahaman dan keterampilan masyarakat dalam mengelola kotoran ternak menjadi pupuk organik. Peningkatan pemahaman masyarakat tentang pupuk organik menjadi 95,65%, peningkatan keterampilan masyarakat dalam membuat pupuk organik menjadi 91,30 %, dan peningkatan kemampuan masyarakat dalam membuat kemasan produk pupuk organik menjadi 86,95%.